The Benefits and Challenges of Globalisation for the Development of Higher Education Teaching and Research: A Case Study of an Emerging University in East Africa. (June 2021) - Tan, Rachel Sing-Ee; Harland, Tony; Daniel, Ben
Globalisation presents the opportunity for universities to have a world-wide presence but newer institutions in developing countries have difficulty in embarking on such a journey. This paper presents a case study of an emerging university in East Africa and explores the challenges of high ambition while responding to globalisation. Interviews with senior administrators and academics showed that much time and effort was spent responding to funding issues and aid conditions, attaining international standards in research and teaching, and managing challenges of digital technologies against a background of limited infrastructure. In response to globalisation, we argue that emerging universities of this type should consider re-directing limited resources to focus on long-term projects for growing human capital through professional development while developing basic infrastructure needs.